Comprehension of the maternal experience during breastfeeding - Rodrigues, Icleia Parente; Queiroz, Maria Veraci Oliveira (Rev Rene, 2005)
Qualitative research with ethnography presuppositions, whose aims are: understanding the meaning of breastfeeding in the lives of breastfeeding women, and apprehending aspects related to the learning experiences lived by the mothers at a Breastfeeding Unit. It was developed in the Breastfeeding Unit of a hospital belonging to the Health Unified System, having as subjects mothers assisted in the Unit under the condition of breastfeeding their children exclusively. The data were obtained from free observation and semi-structured interviews. The analysis of the maternal experiences highlights the socio-cultural aspects resulting from the social interaction, and these women’s experiences as a remarkable phenomenon that implies in the decision to breastfeed, as well as the importance of the teaching-learning process between mothers and health professionals. In the educational investments, however, the technical aspects are emphasized, stressing a hiatus with the socio-cultural factors that contemplate the maternal subjectivity.